Cement stabilization treatment of lead and naphthalene contaminated lateritic soils - Oluwatuyi, Opeyemi E.; Ashaka, Edwin C.; Ojuri, Oluwapelumi O. (Journal of Environmental Engineering and Landscape Management, 2019)
This article presents an investigation on the influence of Ordinary Portland Cement (OPC) as a binder in the stabilization treatment of lateritic soil contaminated with lead or naphthalene. To evaluate the performance of the binder, the contaminated soils were tested for mechanical strength and environmental performance before and after the stabilization treatment. Results showed that the strength as inferred from the unconfined compressive strength (UCS) and cohesion values increased with the addition of the binder. Cement stabilization of the lead contaminated samples also prompted a reduction in the release of lead below the admissible limit during the leaching test. Cement stabilization of the naphthalene contaminated samples, on the other hand, could not contain the release of naphthalene below the regulatory level during the leaching test. The batch equilibrium adsorption test (BEAT) showed that cement stabilization increased the adsorption capacity of the soil for the contaminants.